2018
DOI: 10.1002/cam4.1589
|View full text |Cite
|
Sign up to set email alerts
|

Friend leukemia virus integration 1 is a predictor of poor prognosis of breast cancer and promotes metastasis and cancer stem cell properties of breast cancer cells

Abstract: Breast cancer is the most common cancer in women worldwide; despite the developments in diagnosis and therapy, recurrence and metastasis remain the main causes of death among patients with breast cancer. This study aimed to identify a promising biomarker for this disease. The study clarified (1) the association between Friend leukemia virus integration 1 (FLI‐1) and various molecular subtypes and (2) the prognostic value of FLI‐1 in breast cancer. To the best of our knowledge, this study is the first to report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…FLI1 was first identified as an ETS family member protein that plays a vital role in retroviral-mediated acute leukemias. 45 Accumulating evidence suggested that FLI1 also accelerated the metastasis of nasopharyngeal carcinoma (NPC), 46 breast cancer, 47 and small cell lung cancer, 48 among others. Meanwhile, FLI1 has been well documented to act as an oncogene in Ewing sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…FLI1 was first identified as an ETS family member protein that plays a vital role in retroviral-mediated acute leukemias. 45 Accumulating evidence suggested that FLI1 also accelerated the metastasis of nasopharyngeal carcinoma (NPC), 46 breast cancer, 47 and small cell lung cancer, 48 among others. Meanwhile, FLI1 has been well documented to act as an oncogene in Ewing sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…In PE, when CS are elevated, Na/K-ATPase is depressed and Fli1 is low this results in the occurrence of a phenotype associated with a significantly lower incidence of breast cancer [ 59 , 60 ] ( Figure 2 ). At the same time in breast cancer patients ( Figure 2 ) CS and Na/K-ATPase are regular [ 61 , 62 , 63 , 64 , 65 ] and Fli1 is high [ 66 , 67 , 68 ]; i.e., as if patients with PE administered an anti-CS antibody. Could it be true for the other types of cancer?…”
Section: Immunoneutralization Of Cardiotonic Steroidsmentioning
confidence: 99%
“…When levels of MBG are increased, levels of Fli1 decrease and a Col-1 gene promoter is released from the nucleus and procollagen-1 and collagen become activated [ 32 ]. While many studies have demonstrated that Fli1 is a pro-cancer factor [ 68 , 69 ], CS including MBG are becoming attractive anti-cancer drug candidates [ 70 , 71 ]. It is generally accepted that PE is associated with a low risk of cancer, which is not surprising considering that endogenous levels of MBG and other CS are dramatically increased in PE patients [ 27 , 28 ] and therefore suppress the growth of tumors in vivo and in vitro [ 72 , 73 , 74 ].…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%
“…Interestingly, when levels of CS were compared in the nude mice expressed significantly lower CS concentrations in the adrenal gland and the plasma compared to normal mice [67]. The nude mouse is valuable to research because it can receive many different types of tissue and tumor grafts, as it mounts no rejection response, and it has a very high prognostic value of FLI1 [68,69].…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%